Political Elites as an Object of Coercive Influence in Contemporary World Politics - A. I. Podberezkin; M. V. Kharkevich (Vestnik MGIMO-Universiteta)
Abstract: The article discusses the trend of securitization of the political elite as a reaction to strengthening of coercive influence upon these elites in terms of consolidation and strengthening of confrontation between different civilizations. The authors argue that the main object of the coercive influence in world politics, which ensures stable control of regime change and a managed transit is the political elite rather than civil society. The assumption then is that the main object of the security and the securitization in world politics is to be political elite. Securitization of the political elite can be seen as a necessary condition for ensuring the sovereignty at the level of local human civilization. The conclusion of this paper is, first, the assessment of the political elite as the main object of securitization in a clash of civilizations. Secondly, the removal of contradictions between the securitization of political elites and democracy at the scale of human civilizations; third, underlining the need to take into account the vital importance of the political elite in the strategic planning and development of long-term forecasting of international relations development.